Effect of cigarette smoking on serum α-L-fucose and its related parameters - Yaseen, Neewar Ahmed; Ahmed, Bakhtiar Mohiadeen (Zanco Journal of Medical Sciences (ZJMS), 2014)
Background and objective: Cigarette smoke is a leading preventable cause of many diseases and death, because it contains a complex mixture of chemical compounds. Few studies about the relation between cigarette smoking and glycoconjugate were found in literature, while no study was observed regarding passive smokers. Thus this relation is obscure till now. Therefore this work was designed to study the effect of cigarette smoking on serum glycoconjugates levels. Methods: One hundred twenty one completely healthy males from different areas of Duhok governorate were included in this study. Their age was ranged between 20 and 50 years. They were classified according to the number and duration of cigarette smoking into: heavy smokers (31), moderate smokers (26), passive smokers (30) and non-smokers (control). Fasting blood was withdrawn from all groups and used for determination of serum fucose and its related parameters. Results: The results showed that there was a significant decrease in serum total protein in heavy smoker groups when compared to non-smokers. The levels of serum total fucose and protein bound fucose significantly increased in smoker groups, while the results indicated that there was a significant increase in serum lipid associated fucose levels in heavy and passive smoker groups comparing to non-smoker group. A significant decrease in serum protein bound hexoses was observed in both heavy and moderate smokers. The result also showed that serum total calcium concentration, Ca/TP and Mg/TP ratios significantly decreased in all smoker groups.Regarding to serum Manganese (Mn) and Mn/TP ratio, their values increased significantly in case of passive smokers only. Conclusion: The results revealed that cigarette smoking had significant effects on glycoconjugates status (expressed in serum fucose and its related parameters).